The use of the connective tissue graft from the palate for vertical soft tissue augmentation during submerged dental implant placement: A case series - Imantas Vatėnas; Tomas Linkevičius (Wiley, 2022)
Abstract Objectives To evaluate the efficacy of the soft tissue augmentation vertically, using connective tissue graft from the palate, during submerged dental implant placement. Material and Methods Vertical soft tissue augmentation, using connective tissue graft from the palate, combining with submerged dental implant placement was performed for 50 patients (10 males and 40 females, mean age 57.22 years). Soft tissue thickness vertically was measured in the middle of the alveolar crest with the periodontal probe. After 3 months, healing abutments or multiunits were connected to the dental implants, augmented soft tissue thickness was measured vertically in the middle of the alveolar crest. The vertical soft tissue volume gain was calculated using analysis of variance descriptive analysis, significance set to p = .05. Results All 50 autogenous connective tissue grafts from the palate healed successfully. The average thickness of the soft tissue grafts from the palate was 1.8 ± 0.41 mm. After 3 months, soft tissue thickness vertically increased from 2.27 ± 0.64 mm to 4.35 ± 0.64 mm. This difference between mean figures, between the groups, before and after soft tissue augmentation was found to be statistically significant F (263;477). The mean increase in soft tissue thickness was 2.08 ± 0.71 mm. Conclusion It can be concluded that soft tissue augmentation vertically, using connective tissue graft from the palate can be successfully used for vertical soft tissue augmentation.